The determination of heavy metals in oreochromis mossambica from disused tin-mining pools - Alias Mohd. Yusof, 1951-2014; Khor, Hang Meng; Abdul Khalik Wood; Simposium Kimia Analisis Malaysia (ke-13 : 2000 : Port Dickson, Negeri Sembilan)
10